Whitehead's philosophy of organism and it's cosmological implications in being human - Gianan, Celestino A. (Animo Repository, 1997)
This study deals with tracing the possibility of explaining the reality of being human in the light of the philosophy of organism of Whitehead with the assumptions that being human is organismic in character, that its organismic character makes it dynamistic, and its dynamism characterizes being human in the concrete. The questions to be addressed, therefore, are the following: If being human is organismic in character, how is this character structured using the structure in the organic philosophy of Whitehead? If being human is dynamistic, how is its dynamism patterned after that in the organic philosophy of Whitehead? If being human is concrete, how is its concreteness developed in an organismic and dynamistic environment? The methodology employed in the study is expository and analytic. Much of the exposition will be taken from the philosophy of organism of Whitehead and, in the process, analysis of the said philosophy shall play an important role to achieve the intention of the study.